2012
DOI: 10.1038/eye.2012.192
|View full text |Cite
|
Sign up to set email alerts
|

Eye preservation tectonic graft using glycerol-preserved donor cornea

Abstract: Aims To report the surgical outcome of tectonic graft using glycerol-preserved donor corneas to treat perforated keratitis. Methods The medical records were reviewed of all patients treated for perforated keratitis using glycerol-preserved corneas at a single institution between 1 July 2004 and 31 June 2010. The clinical features, precipitating factors, adjuvant therapies, and therapeutic outcomes were analyzed. Success was defined as re-epithelialization of the ocular surface without evisceration. Results Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
2
30
0
5
Order By: Relevance
“…Lin et al . [ 11 ] demonstrated good cosmetic results utilizing GPC for tectonic keratoplasty with anterior vitrectomy with/without conjunctival flaps as an adequate substitute for evisceration in patients with perforated keratitis. All the patients in their study had little or no visual potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al . [ 11 ] demonstrated good cosmetic results utilizing GPC for tectonic keratoplasty with anterior vitrectomy with/without conjunctival flaps as an adequate substitute for evisceration in patients with perforated keratitis. All the patients in their study had little or no visual potential.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol preservation is a simple technique of long-term storage of acellular corneal tissue, and one of the major benefits of this method is the fact that corneal tissue can be safely preserved up to 5 years after harvesting. [ 11 ] GPC has no viable endothelium and can be used for lamellar corneal transplant that does not require high-quality tissue. GPC can be used in emergencies like perforated corneal ulcer or globe rupture to maintain the globe integrity by therapeutic or tectonic keratoplasty.…”
mentioning
confidence: 99%
“…In addition to all other advantages, glycerol-preserved corneas substantially decreases the cellularity15 and antigenicity of corneal tissues hence minimising any immune rejection12 13 as cells like keratocytes, epithelial cells and other bone-marrow-derived cells are important targets for any allograft response. Various reports have been published delineating that glycerol-preserved donor corneas may be effective substitutes for fresh corneas in patch grafts16 perforated ulcers,17 infectious keratitis,18 eccentric peripheral grafts,19 full-thickness tectonic grafts,20 therapeutic PK3 and to repair exposed glaucoma drainage implants 21. The study by Chen et al concluded that DALK using glycerine-cryopreserved corneal tissue provides clinical results comparable with fresh cornea 13…”
Section: Discussionmentioning
confidence: 99%
“…In the developing countries, glycerin-preserved donor corneas are occasionally grafted for emergent tectonic penetrating keratoplasty. 5 The advantages include lower cost, a lower rate of rejection, and a lower rate of postoperative infections when compared with fresh corneas; the disadvantages to deal with include opacification after reepithelialization, poor visual outcome, and suboptimal esthetic outcomes.…”
Section: Discussionmentioning
confidence: 99%